The Narrative Paradigm in TikTok Content: A Case Study of @Harbie16’s Storytelling Strategy in Reconstructing the Image of a Quiet Restaurant - Angeline Erita Christiani Ngantung; Fabianus Fensi (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
The rapid development of social media, particularly TikTok, has created new forms of digital communication where storytelling serves as a primary means of building emotional engagement and shaping audience perception. A compelling phenomenon is the emergence of content that elevates quiet, empty restaurants and transforms them into narratives rich with values of struggle, hope, and perseverance. The TikTok account @harbie16 consistently employs storytelling to convey narratives about less-popular restaurants, potentially reshaping their public image. This study aims to analyze the narrative elements used in @harbie16's TikTok content, understand the role of storytelling strategies in reconstructing the image of a quiet restaurant, and examine audience interpretations of the conveyed narrative. This research employed an interpretive paradigm with a qualitative approach and a case study method. The primary theoretical framework is Walter Fisher's Narrative Paradigm, specifically the concepts of narrative coherence and narrative fidelity. Data collection was conducted through digital observation of TikTok content, documentation, and analysis of audience responses in the form of comments and other digital interactions. The findings reveal that storytelling, built through elements of characters, conflict, storylines, and solutions, creates coherent and high-fidelity narratives that are well-received by the audience. The narratives play a significant role in shifting negative perceptions of quiet restaurants into a more positive image by forming new meanings based on empathy and shared social experience. This research contributes to the development of digital communication, storytelling, and narrative paradigm studies, and serves as a reference for business actors and content creators in building an image through social media.